Over het aansluiten van puntenvelden (1): Het randefecte lineaire tweede standaard vraagstuk. - Teunissen, Peter; Salzmann, M.A.; de Heus, H.M. (1987)
On the connection of pointfields: In a series of four articles the authors discuss the general problem of connecting geodetic pointfields. The articles give an overview of the necessary statistical theory, treat the connection adjustment and corresponding qualty description and present some worked out practical examples. The first article, titled "The rankdeficient linear second standard problem" discusses the consequences of a rankdeficiency in the design matrix. The relation with the theory of S-transformations and with the adjustment of free networks is shown. In the second article a general method is given for connecting pointfields. In particular, attention is given to rankdeficiencies in the coordinate covariance matrices. The third article discusses the precision and reliability description of the pointfield connection. Finally the fourth article presents some worked out practical examples. Most of the solutions are given in analytical form.